2023
DOI: 10.3233/sw-222896
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies for publishing linked open government data on the Web: A systematic mapping and a unified process model

Abstract: Since the beginning of the release of open data by many countries, different methodologies for publishing linked data have been proposed. However, they seem not to be adopted by early studies exploring linked data for different reasons. In this work, we conducted a systematic mapping in the literature to synthesize the different approaches around the following topics: common steps, associated tools and practices, quality assessment validations, and evaluation of the methodology. The findings show a core set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 86 publications
0
17
0
1
Order By: Relevance
“…However, despite the initially promising expectations, our recent research activities on OGD and LD, involving the analysis of various government portals in different capacities [18,25,46], have occasionally identified what seems to be a significant decline in interest in LOGD. This impression is corroborated by Penteado et al [33], who recently observed, "Although the open government data movement is still producing large amounts of data worldwide, linked data still represents a tiny portion". Attard et al also noted "Yet, the use of Linked Data in open government initiatives is still quite low" [34].…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…However, despite the initially promising expectations, our recent research activities on OGD and LD, involving the analysis of various government portals in different capacities [18,25,46], have occasionally identified what seems to be a significant decline in interest in LOGD. This impression is corroborated by Penteado et al [33], who recently observed, "Although the open government data movement is still producing large amounts of data worldwide, linked data still represents a tiny portion". Attard et al also noted "Yet, the use of Linked Data in open government initiatives is still quite low" [34].…”
Section: Introductionmentioning
confidence: 75%
“…", it is important to recognize the concerns raised by several scholars about the suboptimal adoption of LD and LOD dissemination practices in the government sector, often centered around the limited use of RDF distributions [57][58][59][60]. Despite these concerns, there is a notable scarcity of studies that provide a quantitative analysis of these issues in specific contexts or scenarios [33,[61][62][63]. Among these, Ibanez et al [62], in their analysis of a diverse sample of regional and local European institutional websites, observed that RDF is not widely used.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, other methods focused on how to publish a DMS as linked data and making it interoperable. Towards having high-quality data, Penteado et al (2021) Similarly, Bratsas et al (2021) defined an RDF vocabulary to convert data from a relational database into a knowledge graph. Then, they used this knowledge graph for facilitating ETL (Extract Transform Load) processes and trained a clustering model for identifying red flags in fiscal projects.…”
Section: Related Workmentioning
confidence: 99%